2018
DOI: 10.1007/s00394-018-1651-z
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality in childhood: the Generation R Study

Abstract: Overall diet quality of 8-year-old children did not conform to dietary guidelines, especially for children having more screen time, children of lower educated or smoking mothers, or from lower-income households.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 36 publications
5
69
1
Order By: Relevance
“…Moreover, the intervention group differed significantly from the control group on ethnicity, parental educational level and parental age. Other studies have shown that demographics, such as educational level and ethnicity, are associated with our outcome measures [ 8 , 9 , 75 77 ], and thus might have influenced our results. Another limitation of this design was the difference between the intervention and control group in children’s MVPA and the percentage children consuming fruit and vegetables at school at baseline.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the intervention group differed significantly from the control group on ethnicity, parental educational level and parental age. Other studies have shown that demographics, such as educational level and ethnicity, are associated with our outcome measures [ 8 , 9 , 75 77 ], and thus might have influenced our results. Another limitation of this design was the difference between the intervention and control group in children’s MVPA and the percentage children consuming fruit and vegetables at school at baseline.…”
Section: Discussionmentioning
confidence: 98%
“…Information on child's sport participation (yes; no) and screen time, defined as time spend watching television or computer use (<2; ≥2 h/day), was obtained using a questionnaire at the age of 6 years. Dietary intake of children was assessed at the age of 8 years and we calculated their diet quality score, reflecting adherence to age-specific dietary guidelines [16].…”
Section: Covariatesmentioning
confidence: 99%
“…The methodology to obtain this diet score has been published previously. 20 Screen time and sports participation were assessed by parent-reported questionnaire when the child was 9 years old. Screen time included television viewing, video/DVD use, and computer game use.…”
Section: Diet Screen Time and Sports Participationmentioning
confidence: 99%